2017
DOI: 10.5851/kosfa.2017.37.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Egg Shell and Oyster Shell Powder as Alternatives for Synthetic Phosphate: Effects on the Quality of Cooked Ground Pork Products

Abstract: This study aimed to determine the optimal ratio of natural calcium powders (oyster shell and egg shell calcium) as synthetic phosphate replacers in pork products. Ground pork samples were subjected to six treatments, as follows: control (−) (no phosphate added), control (+) (0.3% phosphate blend added), treatment 1 (0.5% oyster shell calcium powder added), treatment 2 (0.3% oyster shell calcium powder and 0.2% egg shell calcium powder added), treatment 3 (0.2% oyster shell calcium powder and 0.3% egg shell cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…Farinograph parameters of the dough behaviour are related to the composition. e main compound present in egg and oyster shells is calcium carbonate (CaCO 3 ), which is used as an additive in various foods including as a raw material in foods, medicines, and cosmetics and as a calcium source [15]. Chicken egg shell contains proteins as major constituents with small amounts of carbohydrates and lipids and contains approximately 95% calcium carbonate by weight, and 3.5% of the shell is an organic matrix formed from proteins, glycoprotein, and proteoglycans [16].…”
Section: Discussionmentioning
confidence: 99%
“…Farinograph parameters of the dough behaviour are related to the composition. e main compound present in egg and oyster shells is calcium carbonate (CaCO 3 ), which is used as an additive in various foods including as a raw material in foods, medicines, and cosmetics and as a calcium source [15]. Chicken egg shell contains proteins as major constituents with small amounts of carbohydrates and lipids and contains approximately 95% calcium carbonate by weight, and 3.5% of the shell is an organic matrix formed from proteins, glycoprotein, and proteoglycans [16].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate and partial fat replacement resulted in higher b* and h values in all treatments compared to CONF, while signifi cantly higher chroma values were found only in CONC relative to CONF. Bae et al [2017] found no effect of phosphate (0.3%) replacement with 0.5% oyster shell powder on b* values while Cho et al [2017] reported signifi cantly lower yellowness. Though research data indicate that partial replacement of backfat in frankfurters with different oils (stabilised , 2016b], the results of this research show no signifi cant differences within C treatments with in any of the observed colour parameters on day 0.…”
Section: Colour Propertiesmentioning
confidence: 94%
“…Furthermore, nowad ays people are showing a greater interest in foods that contain bioactive or functional components [Hygreeva et al, 2014], and the demand for natural, organic and/ or clean label meat products has also increased. In that sense, sporadic research studies were conducted with natural calcium powders as phosphate substitutes [Cho et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, consumers' perception of healthy foods has been growing, thereby increasing concerns over the safety of synthetic food additives. Consequently, numerous studies have been conducted to find alternatives to synthetic additives in processed meat products (Alahakoon, Jayasena, Ramachandra, & Jo, ; Cho, Bae, & Jeong, ; Jarvis et al, ). As a result, certain synthetic additives, such as sodium nitrite, monosodium glutamate, and other synthetic preservatives, have been replaced by natural materials and introduced to the market successfully (Alahakoon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…meat products (Alahakoon, Jayasena, Ramachandra, & Jo, 2015;Cho, Bae, & Jeong, 2017;Jarvis et al, 2012). As a result, certain synthetic additives, such as sodium nitrite, monosodium glutamate, and other synthetic preservatives, have been replaced by natural materials and introduced to the market successfully (Alahakoon et al, 2015).…”
mentioning
confidence: 99%